Human Suffering as a Multi-perspective Theatrical Image: Hanoch Levin’s The Dreamer, a Study in Writing Contemporary Traged - Yaari, Nurith (MiKAN, 2006)
This article focuses on Hanoch Levin’s The Dreamer (1983), writtenbetween Everybody Wants to Live (1982) and The Lost Women of Troy(1984). Analysis of the central scene of the play (Act I, sc. vii) revealsLevin’s use of three interchanging points of view for his theatricalimage of human suffering: the inter-personal point of view that linksthe victim and his torturer: the metaphysical point of view that linkshuman beings to the metaphysical powers that define human destiny;and the theatrical point of view that links spectators and actors into a"here and now" experience - the performance. As all three points ofview are activated in Ancient Greek, Christian and Modern tragedy, it issuggested that The Dreamer can be read as a contemporary tragedy.